1984
DOI: 10.1159/000457159
|View full text |Cite
|
Sign up to set email alerts
|

Relative Bioavailability of Two Different Phenytoin Preparations

Abstract: Relative bioavailability (RB) of two commercially available phenytoin preparations showed greater differences in absorption in children than in adults. 93 patients received one or more doses of one or two preparations. Serum assays were made at steady state. Age-matched groups were compared. In another cross-over study, 12 patients received two or more doses of each formulation until steady state levels were reached. 5 adult volunteers received single doses of each preparation, and multiple serum samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…As listed in Table IV, 28 studies reported DRBA attributed to age-related absorption (differences in absorption between pediatric and adult populations). Fifteen out of 28 studies reported multiple absorption-related risk factors (8,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), including alterations in GI transit time or motility (8,33,36,38,40,44), changes in GI fluid composition (37,40), and different levels of saturation for intestinal transporters/ metabolism (8,42). Moreover, 11 of the studies from the list of 28 reported factors are also related to the formulations used (32, 34-41, 43, 45), and 5 also related to the drug substance (8,33,38,40,44).…”
Section: Age-related Absorption Effectsmentioning
confidence: 99%
See 4 more Smart Citations
“…As listed in Table IV, 28 studies reported DRBA attributed to age-related absorption (differences in absorption between pediatric and adult populations). Fifteen out of 28 studies reported multiple absorption-related risk factors (8,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), including alterations in GI transit time or motility (8,33,36,38,40,44), changes in GI fluid composition (37,40), and different levels of saturation for intestinal transporters/ metabolism (8,42). Moreover, 11 of the studies from the list of 28 reported factors are also related to the formulations used (32, 34-41, 43, 45), and 5 also related to the drug substance (8,33,38,40,44).…”
Section: Age-related Absorption Effectsmentioning
confidence: 99%
“…Fifteen out of 28 studies reported multiple absorption-related risk factors (8,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45), including alterations in GI transit time or motility (8,33,36,38,40,44), changes in GI fluid composition (37,40), and different levels of saturation for intestinal transporters/ metabolism (8,42). Moreover, 11 of the studies from the list of 28 reported factors are also related to the formulations used (32, 34-41, 43, 45), and 5 also related to the drug substance (8,33,38,40,44). It should be noted that a BE study conducted as a crossover study would cancel out the age-related effects on clearance and highlight those effects that are related to formulation differences; however, due to the limited crossover BE studies conducted in pediatric populations, we summarized all the risk factors related to applying clinical study results from adults to pediatric populations.…”
Section: Age-related Absorption Effectsmentioning
confidence: 99%
See 3 more Smart Citations